2003
DOI: 10.1023/a:1025742423308
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…By contrast, the stringency of employment protection legislation on permanent contract does not seem to play a major role in explaining the decision to move to self-employment in the short or the long term. The result is consistent with Torrini (2005) and Robson (2003). The lack of significance of results is likely to reflect to a large extent the limitation of the measure of employment protections, which is a de jure indicator and captures only imperfectly the stringency of labour-market regulations faced by firms.…”
Section: Unemployment Benefits and Active Labour Market Policies Are Important Drivers Of The Developments In Self-employedsupporting
confidence: 69%
See 1 more Smart Citation
“…By contrast, the stringency of employment protection legislation on permanent contract does not seem to play a major role in explaining the decision to move to self-employment in the short or the long term. The result is consistent with Torrini (2005) and Robson (2003). The lack of significance of results is likely to reflect to a large extent the limitation of the measure of employment protections, which is a de jure indicator and captures only imperfectly the stringency of labour-market regulations faced by firms.…”
Section: Unemployment Benefits and Active Labour Market Policies Are Important Drivers Of The Developments In Self-employedsupporting
confidence: 69%
“…The role that employment protection legislation (EPL) could play in incentivising the choice to work self-employed has also been explored in detail, although the findings have yielded mixed results. A number of studies have shown that EPL restrictiveness has little impact on aggregate self-employment (Robson, 2003;Torrini, 2005;Kannaiainen and Vesala, 2005). However, highlighting the heterogeneity of self-employed as a group, studies that focus on specific categories of self-employmentincluding a negative impact from the interaction between protections and educational attainment (Baumann and Brädle, 2012) -find a significant impact of EPL.…”
Section: Labour Market Policies and Institutionsmentioning
confidence: 99%
“…Finally, one could argue that the reversal in the business ownership rate may be the result of structural changes having strong effects on occupational choice decisions and, therefore, on the elasticity of substitution between paid-employment and self-employment. In particular, we may hypothesise that the above factors, in conjunction with the emergence of incentives schemes, such as subsidies or tax allowances [33][34][35][36][37], and a progressive reduction in the rights and benefits derived from employment protection legislation may have introduced substantial changes in the risk-adjusted relative earnings of paid employment and self-employment [38][39][40][41][42][43][44][45]. Thus, one could argue that higher levels of entrepreneurship may indicate that extant job creators are not creating attractive wage-earning job opportunities as a result of a low valuation of the risk associated with self-employment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Self-employment offers greater opportunities for a reduction in the burden of taxation. The impact that tax policies can have on self-employment has been thoroughly analysed, although the focus has particularly been on the extent to which self-employed individuals mis-report their income to minimise their tax burden (Guyton et al (2018[4]), Åstebro and Chen (2014 [5]), Kleven et al (2011 [6]) and Bárány (2017 [7])). The role that complexities in the labour taxation system can have on self-employment has been explored in great detail in Aghion et al (2017 [8]).…”
Section: Literature Review On the Link Between Self-employment And Pomentioning
confidence: 99%